Sub-acute stent thrombosis and in-stent restenosis associated with antiplatelets clopidogrel resistance and protein s deficiency - Kurniawan, M Zakky; Pratanu, Iswanto (Folia Medica Indonesiana, 2016)
Protein S deficiency and antiplatelets clopidogrel resistance may uncommonly be responsible for coronary artery thrombosis. Hereby we report a patient presented with coronary disease, who had undergone PCI. However, two days later the patient was found in-stent thrombosis. Primary PCI was performed later with good result, but after 4 months evaluation with treadmill test we found significant ST depression in related region. It was suspected the patient had in-stent re-stenosis incidence. Further hematologic investigation showed that this patient had antiplatelets clopidogrel resistance and protein S deficiency. Double antiplatelet with another kind of antiplatelets and anticoagulant had given in this case. However, the remaining consideration is the choice for reperfusion strategy.